2016
DOI: 10.5860/crl.77.5.614
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Use of Google vs. Library Resources: A Four-Year Cohort Study

Abstract: . © 2016 Carol Perruso, Attribution-NonCommercial (http://creativecommons.org/licenses/by-nc/3.0/) CC BY-NC. This longitudinal study at a large public university surveyed students of the 2008 freshmen cohort over four years about their use of websites and library resources for their research papers. The three goals of the study were to track changes in reported research behavior over time, to see if students' reported source choices were associated with librarian instruction and/or if they were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
(13 reference statements)
0
10
0
1
Order By: Relevance
“…Sometimes called ‘pathways’ (Gardner & Inger, ) and sometimes presented as ‘journeys’ (Faherty, ), information professionals are striving to understand what content channels are being employed by all types of academic users and buyers. The reports highlighted here demonstrate how preferred channels vary depending on training, discipline, or cultural background – whether by looking at Google‐trained US undergraduate students (Perruso, ) or measuring the rates by which US lecturers start their search for new content in their institutional libraries (Wolff et al ., ). These trends differ again when looking at methods for measuring information seeking of Jordanian humanities scholars, who often rely on peer recommendations as a discovery starting point (Al Shboul & Abrizah, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes called ‘pathways’ (Gardner & Inger, ) and sometimes presented as ‘journeys’ (Faherty, ), information professionals are striving to understand what content channels are being employed by all types of academic users and buyers. The reports highlighted here demonstrate how preferred channels vary depending on training, discipline, or cultural background – whether by looking at Google‐trained US undergraduate students (Perruso, ) or measuring the rates by which US lecturers start their search for new content in their institutional libraries (Wolff et al ., ). These trends differ again when looking at methods for measuring information seeking of Jordanian humanities scholars, who often rely on peer recommendations as a discovery starting point (Al Shboul & Abrizah, ).…”
Section: Resultsmentioning
confidence: 99%
“…The modes of discovery can also fluctuate based on type of user and their task at hand. For instance, an undergraduate student doing a term paper might start with an open, keyword search in the open web, then narrow down to citable works with the help of the library – routines which are shown to improve with additional research training by the library (Perruso, ). Many reports address distinct types of search activity – such as a student searching for known items discovered via a citation or course syllabi or a medical practitioner exploring related material by the same author via a subject database.…”
Section: Resultsmentioning
confidence: 99%
“…Los estudios centrados en estudiantes de doctorado o jóvenes investigadores son relevantes habida cuenta de que se trata de conocer las actitudes de las nuevas generaciones de investigadores, sin duda aquellos con mayores habilidades tecnológicas, pues han crecido con internet proporcionándoles información con facilidad e inmediatez. Los principales resultados obtenidos del primer año de la investigación del proyecto Harbingers sobre descubrimiento de información científica son los siguientes (Nicholas et al 2017 Según van avanzando en su carrera, los estudiantes universitarios tienden a utilizar más los recursos de la biblioteca (Perruso, 2016) El estudio de Pontis et al (2015) basado en entrevistas a 61 investigadores de categorías y antigüedad variable indica que la experiencia determina los canales utilizados en la búsqueda de información. Así, los jóvenes investigadores, poco expertos, mayoritariamente buscan información relevante en la Web.…”
Section: Dónde Y Cómo Encuentra La Comunidad Académica La Informaciónunclassified
“…And these global search engines are not just deployed to answer every day questions but have become a starting point (and, sometimes, an end point) from much scholarly research. There is much published research to that effect; so, for example, Perruso () reported that 70% of first‐year undergraduates start with a general web search (although that declines as students go through their course), whilst Housewright (2013), in a large‐scale survey in 2012, reported that over 30% of library users will start with a general search engine in preference to a library web site or other tools. Wolff, Rod, and Schonfeld (), in the Ithaka longitudinal series of studies, show web search engines to have been the primary route for search since 2010, and that continues today.…”
Section: Library Discovery Systemsmentioning
confidence: 99%